Detecting entanglement can be more effective with inequivalent mutually unbiased bases. (13th September 2021) - Hiesmayr, B C; McNulty, D; Baek, S; Singha Roy, S; Bae, J; Chruściński, D
Abstract: Mutually unbiased bases (MUBs) provide a standard tool in the verification of quantum states, especially when harnessing a complete set for optimal quantum state tomography. In this work, we investigate the detection of entanglement via inequivalent sets of MUBs, with a particular focus on unextendible MUBs. These are bases for which an additional unbiased basis cannot be constructed and, consequently, are unsuitable for quantum state verification. Here, we show that unextendible MUBs, as well as other inequivalent sets in higher dimensions, can be more effective in the verification of entanglement. Furthermore, we provide an efficient and systematic method to search for inequivalent MUBs and show that such sets occur regularly within the Heisenberg–Weyl MUBs, as the dimension increases. Our findings are particularly useful for experimentalists since they demonstrate that a clever selection of MUBs allows for entanglement detection with fewer measurements.